Relationship between website quality and user willingness to donate to non-profit organizations - Ibrahim, Muhamad Shamsul (2017)
The advancement of communication technology has brought new horizon of business approach in this digital era. A non-profit organization needs a better understanding to manipulate website online factors to meet website user preference and to influence their decision making. This study uses website quality and Technology Acceptance Model (TAM) to identify the relationship of online factors for a website with website user willingness to donate. The aim of this study is to identify the online factors preferred by the NPO website user. This study use frequency as first statistical analysis to measure the presence of the website quality features in the NPO website that involved in this study. The study also using SEM as it second statistical analysis to explore the relationship between the variables. In addition, this study also tested the significance of satisfaction of using NPO website as a mediator between the website online factors with user willingness to donate. The study uses a mixed method namely a survey and quantitative content analysis as a research design. The survey was the main method and conducted online for users from the ten non-profit organisation that involved in this research. The study adopted a convenience sampling technique. The selected respondent must have an experience browsing the NPO website. Therefore, 269 responses were successfully collected. While the quantitative content analysis was a supplement method and used to measure the presence of the website quality features on the similar NPO participated in this study. For the information quality features, a descriptive analysis showed all the NPO in this study has included the NPO general information, also parallel with a website user level of importance. While for the system quality features, the finding revealed that every NPO website participated in this study have included a menu option on their website for better navigation to the next website page. The finding also is equivalent to the respondent level of importance. Whereas, for the service quality, 90% of the NPO have included telephone and fax number on the website to establish two-way communication with website users. The finding corresponds to the website user level of importance. For the variables relationship, the finding indicated only service quality was found related to user satisfaction of using the NPO website. In addition, the satisfaction of using the NPO website also significantly related to the website user willingness to donate. Hence, the satisfaction of using NPO website showed an indirect relationship between service quality and user willingness to donate. While trust and system quality showed a direct relationship to user willingness to donate. This study concluded that website users are willing to donate if they feel satisfied with the NPO website service. The website users also are willing to donate if the NPO website can be trusted and the website system quality met their expectation. Therefore, service, system and trust quality are important to be considered if the NPO to develop a website.